Commentary: Physiological and psychological impact of face mask usage during the COVID-19 pandemic - Scheid, J. L.; Lupien, S. P.; Ford, G. S.; West, S. L. (International Journal of Environmental Research and Public Health, 2020)
In this commentary, we discuss the physiological effects of wearing masks for prolonged periods of time, including special considerations, such as mask wearing among those who engagein exercise training, and concerns for individuals with pre-existing chronic diseases. In healthy populations, wearing a mask does not appear to cause any harmful physiological alterations, and thepotentially life-saving benefits of wearing face masks seem to outweigh the documented discomforts (e.g. headaches). However, there continues to be controversy over mask wearing in the United States, even though wearing a mask appears to have only minor physiological drawbacks. While there are minimal physiological impacts on wearing a mask, theoretical evidence suggests that there may be consequential psychological impacts of mask wearing on the basic psychological needs of competence, autonomy, and relatedness. These psychological impacts may contribute to the controversy associated with wearing masks during the COVID-19 pandemic in the United States. After we discuss the physiological impacts of mask wearing, we will discuss psychological effects associated with wearingmasks during the COVID-19 pandemic.